2015
DOI: 10.1007/s11626-014-9865-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone responsive protein spot 14 enhances lipogenesis in bovine mammary epithelial cells

Abstract: Thyroid hormone responsive spot 14 (THRSP, Spot14, S14) is a nuclear protein that regulates milk fat synthesis. To investigate the role of THRSP in lipogenesis in the dairy cow mammary gland, first, we examined the association between milk fat concentration and THRSP expression in the mammary gland. We found that the dairy cow mammary glands that produced milk with high fat had high THRSP mRNA and protein levels. Additionally, the study described the consequences of overexpression or depletion of THRSP on lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
3
25
1
Order By: Relevance
“…Expression of S14 is controlled by nutritional and hormonal factors and is restricted to liver and adipose tissue, particularly in lipomatous nodules. Suggestive of a role in lipid metabolism, it is also expressed in lipogenic breast cancers (Moncur et al, 1998) and upregulates lipogenesis in bovine mammary epithelial cells (Cui et al, 2015)…”
Section: Resultsmentioning
confidence: 99%
“…Expression of S14 is controlled by nutritional and hormonal factors and is restricted to liver and adipose tissue, particularly in lipomatous nodules. Suggestive of a role in lipid metabolism, it is also expressed in lipogenic breast cancers (Moncur et al, 1998) and upregulates lipogenesis in bovine mammary epithelial cells (Cui et al, 2015)…”
Section: Resultsmentioning
confidence: 99%
“…Very recently it was demonstrated in bovine mammary epithelial cells that the overexpression of Spot14 increases TAG synthesis and the expression of FASN, SREBF1, and PPARG (57). Opposite results were obtained from the inhibition of Spot14 expression (57). It remains to be determined whether Spot14 is able to bind directly to the promoter region of any milk-fat related genes, including SREBF1 and PPARG, and if it can bind and be directly activated or inhibited by nutrients, including LCFA.…”
Section: Other Tfmentioning
confidence: 97%
“…In Spot14-null and Spot14-overexpressing mice, it was observed that only a decrease of milk fat synthesis in the former and an increase in the proportion of medium-chain FA in milk TAG in the latter (but no change in total milk fat) occurred. In addition, the main finding was that there was increased activity of fatty acid synthase without any effect on expression of proteins involved in milk fat synthesis (57).…”
Section: Other Tfmentioning
confidence: 99%
“…Thyroid hormone-inducible hepatic protein (THRSP) was upregulated on days 21 and 42 with OO (Table 4), whereas this protein was upregulated on day 42 and downregulated on day 63 with HVO ( Table 5). Cui et al [29] reported that dairy cow mammary glands producing milk with high fat content could have high THRSP mRNA and protein levels. They also observed that mammary epithelial cells with overexpressed THRSP can increase TAG levels and enhanced abundance of FASN, PPARG, and SREBP1, resulting in a critical role in de novo lipogenesis and consequently influencing milk fat synthesis.…”
Section: Genementioning
confidence: 99%